Mind Style and Motherhood in 21st Century Philippine Fiction - Erly S. Parungao Callueng; Jennie V. Jocson (Faculty of Teacher Training and Education, Universitas Terbuka, 2021)
This paper presents an analysis of Isolde Amante’s Eve, a 21st century Philippine fiction to reveal a contemporary worldview of motherhood. Despite the success of feminist movements in society, motherhood remains fraught with romantic ideals that stem from the essentialist notions of gender and sex. This results in ‘othering’–oppressing and alienating women in the 21st century. The paper argued that the entire notion of motherhood has entered a postmodern framing—one that challenges traditional notions of motherhood and mothering. To characterize this worldview, the paper used the theories of cognitive stylistics, such as conceptual metaphor theory, to describe the mind style of the text’s focalizer, the narrator in Eve. This theory granted access to the intricate mental processes which helped explain why a character behaves a certain why, what dispositions s/he hold in life, as well as what motivations form his/her thoughts, language and action. Further, the mind style is drawn from the communicative force that make up the ‘maternal discourse’ in the text, using Searle’s Speech Act theory. The result is an unorthodox but liberating view of motherhood and mothering. The study argues the need to mainstream mind style analysis in 21st century fiction literary analysis to discover evolving and liberating ideals related to the constructions of gender, and in particular, motherhood.